Change the Routine: Report on the Independent Review into Gymnastics in Australia (2021)
Gymnastics Australia engaged the Australian Human Rights Commission (the Commission) in August 2020 to conduct an independent review of culture and practice at all levels of the sport of gymnastics in Australia. The Independent Review into Gymnastics in Australia (the Review) was requested by Gymnastics Australia following the release of the documentary `Athlete A`. The documentary sparked a global sharing of experiences of abuse in the sport, via social media, with several former athletes and parents of former athletes coming forward in Australia. By engaging with members and former members across the gymnastics community in Australia, and undertaking a high-level evaluation of policy and procedures, the Review led to a comprehensive understanding of the culture of the sport, including systemic risk factors for child abuse and neglect, misconduct, bullying, abuse, sexual harassment and assault towards athletes. Some of these risk factors also exist in many other sports, including significant power disparities between athletes and coaches and administrators. However, the Commission found that unique facets of gymnastics, including the extremely high proportion of young female athletes, contribute to a high-risk environment for abuse and for the maintenance and reinforcement of negative societal stereotypes and ideals around gender. Placing the voices of children and young people and their families at the centre, this report outlines the Commission`s key findings and presents 12 recommendations for whole of sport change. The implementation of the Commission`s recommendations requires engagement and action across all levels of the sport. Such action will be a step towards achieving transformative cultural change and ensuring that the human rights of gymnasts across Australia are upheld. As a sport where the participants are predominantly young girls and women, there is an opportunity for gymnastics to play a societal role in driving gender equality and challenging stereotypes of how young women and girls should behave and appear. Gymnasts have always been strong, powerful and capable. It is time for gymnastics as a global sport to recognise and celebrate this fact. The Commission also identified a `win-at-all-costs` culture that prevailed across the sport and found that this created unacceptable risks for the safety and wellbeing of often very young gymnasts. Gymnastics at all levels of the sport—national, state and club—has a responsibility to put the wellbeing and safety of all athletes, particularly those who are children and young adults, at the forefront of everything it does. Effective cultural change for every athlete in every gym across the country will only be realised when strong leadership at all levels of the sport commit to a collaborative and holistic approach to addressing the challenges outlined in this report. Each section of the report focuses on a distinct aspect of the sport`s culture and includes analysis of the main identified challenges. Summary of findings and recommendations